The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00264-009-0894-y
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint arthroplasty after tibial osteotomy

Abstract: A total of 29 consecutive knee joint arthroplasties in 24 patients who underwent previous high tibial osteotomy (HTO) for medial unicompartment osteoarthritis of the knee and followed up for a mean of 97 months were compared with a control group of 28 patients with 29 primary total knee arthroplasty (TKA) without previous HTO. Results for the osteotomy group were satisfactory in 96.5% of cases. In one patient loosening of the implant occurred after 37 months, which required prosthesis revision. Three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
3
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 27 publications
0
38
3
9
Order By: Relevance
“…Additional techniques to facilitate exposure were required in 7 patients being 3 quadriceps snips, 3 lateral releases and 1 tibial tubercle osteotomy. The Caton index was also significantly reduced in the study group post-operatively, in which 3 patients required subsequent patella resurfacing at 18, 19 and 27 months with the authors suggesting that primary patella resurfacing be considered in these patients to reduce rates of anterior knee pain (Amendola 2010).…”
Section: High Tibial Osteotomy and Conversion To Total Knee Arthroplastymentioning
confidence: 79%
“…Additional techniques to facilitate exposure were required in 7 patients being 3 quadriceps snips, 3 lateral releases and 1 tibial tubercle osteotomy. The Caton index was also significantly reduced in the study group post-operatively, in which 3 patients required subsequent patella resurfacing at 18, 19 and 27 months with the authors suggesting that primary patella resurfacing be considered in these patients to reduce rates of anterior knee pain (Amendola 2010).…”
Section: High Tibial Osteotomy and Conversion To Total Knee Arthroplastymentioning
confidence: 79%
“…It is generally accepted that TKA after HTO is technically more difficult (10,11); however, there is still disagreement whether the subsequent TKA is compromised. Although several comparative studies showed contradictory results; some (1,2,10,(12)(13)(14) suggesting that prior HTO does not change later TKA outcome and others (5,11,15,16) concluding that the converse is true.…”
Section: Introductionmentioning
confidence: 93%
“…High tibial osteotomy (HTO) is an established method to treat medial unicompartmental osteoarthritis (OA) of the varus knees in young and middle-aged patients (1)(2)(3)(4). Rationale for the HTO is based on mechanical axis change of the lower limb, with load stress transfer from the pathological medial compartment to the still healthy lateral side (2,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Açık kama osteotomisi sonrasında uygulanacak bir artroplasti için, mediyal parapatellar insizyon yeterli olabilir. [3] Ancak, aynı durum kapalı kama osteotomisi için geçerli değildir. Bu durumda, longitudinal insizyona 60-90º arasında oblik insizyon yapılması ya da çoklu insizyonlar arasında 7 cm'lik aranın korunması, nekroz riski oluşturmadan lateral tibial bölgeye ulaş-maya ve buradaki implantların çıkartılmasına olanak sağlayabilir.…”
Section: Yüksek Ti̇bi̇al Ostetomi̇ Sonrasi Di̇z Protezi̇ İle Revi̇zyonunclassified